BURNOUT SYNDROME AND ENGAGEMENT, A DESCRIPTIVE STUDY IN PUBLIC SECTOR WORKERS - Tirso Javier Hernandez Gracia; Dolores Margarita Navarrete Zorrilla; Ma. del Rosario Garcia Velazquez; Sergio Demetrio Polo Jimenez; Ventura German Sanchez Monjaraz; Alejandra Corichi Garcia (European Scientific Journal, ESJ, 2013)
This research was conducted in 300 public sector administrative workers in the State of Hidalgo, México. The objective was to determine the levels of Burnout (MBI) and Engagement (UWES) that may be present in such personnel. The results show that 45.3% of employees have a high level of Burnout in the emotional exhaustion dimension and 60% show a medium level in the dimension, dedication of Engagement.